The mineralizing fluid in the Piaba gold deposit, São Luís cratonic fragment (NW-Maranhão, Brazil) based on fluid inclusion studies in quartz veins - FREITAS, Saney Cecílio Ferreira de (2015)
Piaba is the first gold mine to operate in the São Luís cratonic fragment, NW-Maranhão, northern Brazil. The geological setting comprises chiefly metavolcano-sedimentary sequences (Aurizona Group) and subduction-related granitoids (Tromaí Intrusive Suite), formed in island arc between 2240 and 2150 Ma. Gold mineralization is hosted in a fine-grained granophyric granodiorite (Piaba Granophyre) and in a subvolcanic andesite of the Aurizona Group. The mineralized zone is confined within the limits of the Piaba fault (ENE-WSW-trending brittle-ductile shear zone) and consists of quartz veins and veinlets and accompanying hydrothermal haloes (chlorite + muscovite + carbonate + pyrite + chalcopyrite + gold) disposed in stockwork geometry. Petrographic, microthermometric and microRaman spectroscopic studies of quartz have defined two- and three-phase aqueous-carbonic fluid inclusions produced by heterogeneous trapping during phase separation, in addition to late aqueous fluids. The mineralizing solution is an aqueous-carbonic fluid composed of CO2 (5 - 24 mol%), H2O (74 - 93 mol%), N2 (< 1 mol%) and CH4 (< 1mol%). It presents low salinity (5.5 wt.% NaCl equivalent) and density of 0.96 - 0.99 g/cm3). Ore deposition occurred at 267 - 302ºC and 1.25 - 2.08 kbars, corresponding to 4 - 7 km in depth, in agreement with the structural information. The P-T-X and reduced characteristics (log ƒO2 -31.3 to -34.3) of the fluid, combined with host rock sulfidation, altogether indicate that gold has been transported as a sulfur complex and that ore deposition occurred in response to phase separation and lowering of the sulfur activity and ƒO2 during fluid-rock interaction.